Two manuscript versions of Tadeusz Różewicz’s Kartoteka - Zbigniew Władysław Solski (Przestrzenie Teorii)
This article discusses two handwritten versions of Tadeusz Różewicz’s Kartoteka (The Card Index) from the manuscript of the play which since the 70s is to be found in Professor Józef Kelery’s archive. The range of differences between the manuscript and the printed version of the drama is comparable as between Kartoteka (The Card Index) and Kartoteka rozrzucona (The Scattered Card Index). In the manuscript the author distinguished Kartoteka (The Card Index) and Odmiana tekstu (The Kind of Text). A similar division into Kartoteka (The Card Index) and Odmiana tekstu (The Kind of Text) was used by the poet when the works were printed in 1971. Loose pages from Odmiana tekstu (The Kind of Text) contain unordered fragments of the play of written in 1957. These are mainly variants of conversations of the Hero with the Choir in which the author referred to the then vivid debate on the poetic drama. Mieczysław Kotlarczyk was made a hidden partner of discussion and disguised the Choir as actors of Teatr Rapsodyczny (The Rhapsodic Theatre). On the other hand, Kartoteka (The Card Index) of 1958 is a well-ordered and coherent paginated text by the author himself. In this version the author divided the play into three acts, putting most emphasis on the scene of the Wielki Egzamin (A Big Exam). He also removes unrealistic motifs, among other things, the scene when the Choir participates. The poet writes about the peerelowska (Polish People’s Republic’s the reality with the passion of a political commentator, referring to political harassment).